Analisis Problematika Dalam Membaca Al-Qur’an Pada Mahasiswa Semester 8 Jurusan Pendidikan Agama Islam Di Institute Agama Islam Negeri (Iain) Ternate - Eku, Amran (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to identify the problems faced by 8th semester students majoring in Islamic Religious Education at IAIN Ternate in reading the Qur'an. Some of the problems identified involve difficulties in reading Arabic letters, improper pronunciation, as well as inadequate understanding of tajweed. To address these problems, this study used a qualitative approach by collecting data through interviews and observations of 9 students. The results show that some students have good Qur'an reading skills, while others have difficulties. Factors such as educational background, motivation, curriculum and support play an important role in the ability to read the Qur'an. This study provides a comprehensive picture of the actual situation and provides a basis for future improvement of the education system